2012
DOI: 10.1093/intimm/dxs043
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity of ginsenoside Rg3 in promotion of the immune response to ovalbumin in mice

Abstract: Our previous investigation demonstrated that ginsenoside Rg3 was active in promotion of the immune response. In this study, two epimers, 20(R)-Rg3 and 20(S)-Rg3, were compared for their adjuvant effects on the immune response against ovalbumin (OVA). BALB/c mice were immunized subcutaneously with 10 μg of OVA alone or with 10 μg of OVA mixed in 20(R)-Rg3 (50 μg) or 20(S)-Rg3 (50 μg) on days 1 and 15. Two weeks after the last immunization, blood was sampled to test IgG and the IgG subclasses as well as IFN-γ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…It has been used widely as a tonic for various disorders in China, Korea and Japan for over two thousand years and is now a popular herbal remedy worldwide. Ginsenosides, the bioactive ingredients of ginseng, have been proven to provide therapeutic effects affecting the cardiovascular, endocrine, immune, and central nervous systems [6,7,8,9]. Ginsenosides are generally classified into two categories, namely the panaxadiols and the panaxatriols.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used widely as a tonic for various disorders in China, Korea and Japan for over two thousand years and is now a popular herbal remedy worldwide. Ginsenosides, the bioactive ingredients of ginseng, have been proven to provide therapeutic effects affecting the cardiovascular, endocrine, immune, and central nervous systems [6,7,8,9]. Ginsenosides are generally classified into two categories, namely the panaxadiols and the panaxatriols.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer is one of a diverse group of steroidal saponins with high pharmacological activity [16]. Stereospecific effects have been observed from this compound, with the 20(R) enantiomer, for instance, being more active as an antioxidant and in its promotion of the immune response [17, 18], and the 20(S) having a greater potential anti-diabetic activity [19]. While the 20(R) enantiomer of this compound is poorly soluble, the 20(S) enantiomer has a much higher solubility, thus making it more suitable for pharmaceutical development.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, Rg 3 has been shown to be a potential adjuvant in OVA-immunized BALB/c mice. 27 In this study, we showed that F3, the deglycosylated ginsenoside-enriched fraction fractionated by SC-CO 2 , composed of Rh 1 , Rh 2 , and Rg 3 , exhibited the highest antiinflammatory ability in THP-1 cells compared to the other tested fractions.…”
Section: Notesmentioning
confidence: 65%